Selection of suitable species as a key factor for vegetation restoration of degraded areas in an open‐pit manganese‐ore mine in Southern China using multivariate‐analysis methods. (27th February 2019) - Hou, Xiaoyun; Liu, Shiliang; Zhao, Shuang; Beazley, Robert; Cheng, Fangyan; Wu, Xue; Xu, Jingwei; Dong, Shikui
Abstract: Open‐pit mining results in large amounts of degraded lands that require ecological recovery. Adequate‐species selection for ecological recovery is of great importance. In this study, field investigations along the disturbance gradients (marginal area, restoration area, and control area) in a manganese ore deposit of Guangxi in Southern China were carried out. We screened the adequate species from two aspects. In the marginal area, the result of corrected Akaike information criterion revealed that Mn was the most important soil parameter affecting vegetation diversity. Cyclosorus parasiticus (L.) Farwell., Setaria viridis (L.) Beauv., Mimosa sepiaria Benth., and Bidens pilosa L. were selected for their abilities to adapt to high‐Mn‐content soils. In the restoration area and control area, we combined important values and field performance (Dickson quality index, DQI) of species to select adequate species. Miscanthus sinensis Anderss. and Arundinella hirta (Thunb.) Tanaka were selected using the similar DQI ( p > 0.05) in both areas. In summary, C. parasiticus (L.) Farwell., S. viridis (L.) Beauv., M. sinensis Anderss., and A. hirta (Thunb.) Tanaka were selected as adequate species because of their high potential to adapt to these disturbed sites. Our results and methodology could have a demonstrating effect for restoration programmes in manganese ore mining areas of China.